2019
DOI: 10.21685/1680-0826-2019-13-3-6
|View full text |Cite
|
Sign up to set email alerts
|

Amoeba proteus and ploidy cycles: from simple model to complex issues

Abstract: This short topical review/opinion paper is inspired by the recent study of Amoeba proteus cell cycle. These obligate agamic amoebae have a special type of cyclic polyploidy-an alternation of unproportional polyploidization and depolyploidization, with the latter provided by chromatin extrusion from the nucleus into the cytoplasm. Here we discuss possible significance and mechanisms of this phenomenon, reconsider similar strategies of life cycles in other unicellular eukaryotes, and debate provocatively the fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…IM coupling to telomere maintenance by ALT (or even substituting it) could resolve the long-standing puzzle of the Muller's Ratchet [95] in the obligately agamic amoeba existing on Earth for eons. They undergo cyclic polyploidy accompanied by chromatin diminution and express the orthologs of genes employed in meiosis of sexual eukaryotes Spo11, Mre11, Rad50, Rad51, Rad52, Mnd1, Dmc1, Msh, and Mlh [83,87,[96][97][98][99]. Archetti [100] recently presented calculations showing that asexual reproduction can replace sexual reproduction with inverted meiosis due to recombinative gene conversion, providing protection from the deleterious loss of heterozygosity and outweighing the cost of sex.…”
Section: Discussionmentioning
confidence: 99%
“…IM coupling to telomere maintenance by ALT (or even substituting it) could resolve the long-standing puzzle of the Muller's Ratchet [95] in the obligately agamic amoeba existing on Earth for eons. They undergo cyclic polyploidy accompanied by chromatin diminution and express the orthologs of genes employed in meiosis of sexual eukaryotes Spo11, Mre11, Rad50, Rad51, Rad52, Mnd1, Dmc1, Msh, and Mlh [83,87,[96][97][98][99]. Archetti [100] recently presented calculations showing that asexual reproduction can replace sexual reproduction with inverted meiosis due to recombinative gene conversion, providing protection from the deleterious loss of heterozygosity and outweighing the cost of sex.…”
Section: Discussionmentioning
confidence: 99%
“…In turn, the early embryonal development in mammals also bears the phylogenetic features of the transition from unicellular to multicellular organisms. This transition evolved little new genes and it was mostly operating with multi-nuclearity, transient colonial forms, ploidy cycles [145,146], chromatin diminution [147], facultative sex [148], and asexual reproduction [149,150]. Interestingly, the earliest tumours were discovered within the same evolutionary forms, in basic metazoan Hydra, the authors concluded: "cancer is as old as multicellular life on Earth" [151].…”
Section: Cancer Cells Recapitulate the Stress-adaptive Programs Of Unmentioning
confidence: 99%
“…DNA content as well as nucleoli, heterochromatin and gonosomal chromatin bodies distributed into "subnuclei" according to their ploidy levels [3,[27][28][29][30]. By now, it is possible to consider it as variant of so called "polyploidy cycle" [31][32][33] that implies alternation of diploid and polyploid state in a cell lineage. It should be noted that such a phenomenon is fairly rare encountered in the cell lifespan and may be found in the "ancient" organisms like Protists [31][32][33] and some Invertebrates [34].…”
Section: Poly-and Aneuploidy Their Origin and Significancementioning
confidence: 99%